1995
DOI: 10.1161/01.cir.91.12.2924
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Kinetics of Recovery of Oxygen Consumption After Maximal Graded Exercise in Patients With Chronic Heart Failure

Abstract: Postexercise T1/2 VO2 increases when CHF worsens, perhaps in part a result of slower kinetics of recovery of muscle energy stores. The time course of oxygen consumption recovery may represent a simple new criterion for measuring the impairment of the circulatory response to exercise in CHF, even submaximal exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
176
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(199 citation statements)
references
References 62 publications
16
176
0
7
Order By: Relevance
“…Similar findings have been also demonstrated in chronic left heart failure patients. 40,41 These results may indicate an abnormal oxygen delivery to the peripheral tissues mainly from an impaired cardiac output during exercise or peripheral tissue oxidative mechanism impairment. The strong correlation between CR and HRR 1 with peak exercise oxygen uptake BMI, body mass index; FEV 1 , forced expired volume in 1 second; FVC, forced vital capacity; HR, heart rate; %CR, (peak HR-resting HR/220-age-resting HR) Â 100; HRR 1 , the difference between peak HR and HR 1 minute later; VO 2 p, peak oxygen uptake; AT, anaerobic threshold; WRp, peak work rate; VO 2 -t/slope, the first-degree slope of VO 2 for the first minute of recovery; VE/VCO 2 slope, the slope of the ventilatory equivalent for carbon dioxide output; P ET CO 2 , end-tidal expiratory partial pressure for carbon dioxide output; SaO 2 , pulse oxygen saturation; CI, cardiac index; RAP, right atrial pressure; mPAP, mean pulmonary artery pressure; PCWP, pulmonary capillary wedge pressure; i, idiopathic; ii, PAH associated with scleroderma; iii, atrial septal defect; iv, Rendu-Osler-Weber disease.…”
Section: Discussionmentioning
confidence: 98%
“…Similar findings have been also demonstrated in chronic left heart failure patients. 40,41 These results may indicate an abnormal oxygen delivery to the peripheral tissues mainly from an impaired cardiac output during exercise or peripheral tissue oxidative mechanism impairment. The strong correlation between CR and HRR 1 with peak exercise oxygen uptake BMI, body mass index; FEV 1 , forced expired volume in 1 second; FVC, forced vital capacity; HR, heart rate; %CR, (peak HR-resting HR/220-age-resting HR) Â 100; HRR 1 , the difference between peak HR and HR 1 minute later; VO 2 p, peak oxygen uptake; AT, anaerobic threshold; WRp, peak work rate; VO 2 -t/slope, the first-degree slope of VO 2 for the first minute of recovery; VE/VCO 2 slope, the slope of the ventilatory equivalent for carbon dioxide output; P ET CO 2 , end-tidal expiratory partial pressure for carbon dioxide output; SaO 2 , pulse oxygen saturation; CI, cardiac index; RAP, right atrial pressure; mPAP, mean pulmonary artery pressure; PCWP, pulmonary capillary wedge pressure; i, idiopathic; ii, PAH associated with scleroderma; iii, atrial septal defect; iv, Rendu-Osler-Weber disease.…”
Section: Discussionmentioning
confidence: 98%
“…While our data demonstrate that skeletal muscle oxidative capacity is not reduced in our cohort of CHF patients it is possible that the rate of oxidative phosphorylation during exercise is reduced. In vivo studies using P-31 nuclear magnetic resonance (P-31 NMR) spectroscopy have demonstrated reduced phosphocreatine (PCr) resynthesis post-exercise in CHF patients 27,41 . As PCr resynthesis is an oxidative process, this suggests an impaired rate of oxidative phosphorylation.…”
Section: Muscle Fiber Types Muscle Biopsy Studies In Chf Have Consismentioning
confidence: 99%
“…Then 50% of that change was calculated and subtracted from the energy expenditure for reading. The calculated oxygen consumption then was compared to oxygen consumption during recovery at one-minute and twominute intervals to identify the number of individuals in each group who achieved 50% recovery at those time points (Scrutinio, Passantino, Lagioia, Napoli, Ricci, & Rizzon, 1998;Cohen-Solal, Laperche, Morvan, Geneves, Caviezel, & Gourgon, 1995).…”
Section: Extraction Of Reading Metabolic Recovery Datamentioning
confidence: 99%
“…Data on EPOC will provide insight into the cardiac output that aids in recovery from exercise -that is, around cardiovascular recovery issues (Cohen-Solal et al, 1995).…”
Section: Descriptive Exploration Of Raw Data (Supplement To Sa 1)mentioning
confidence: 99%